Climate Change Adaptation Strategies Vary With Climatic Stress: Evidence From Three Regions of Vietnam - McKinley, Justin D.; LaFrance, Jeffrey T.; Pede, Valerien O. (Frontiers in Sustainable Food Systems, 2021)
Vietnam faces several adverse climatic stresses such as increases in temperature, drought, flooding, saltwater intrusion, and sea-level rise. Past research on climate change adaptation in Vietnam has highlighted that climatic stresses and challenges faced by populations vary across the country. In this study, we are interested to know if autonomous responses also vary, depending on which stress individuals are responding to. To answer this question, we use primary-collected data of 1,306 individuals from the Mekong River Delta, Central Vietnam, and the Red River Delta. Adaptation choices of these individuals are analyzed at two levels: the household-level and the agricultural-level. We estimate multivariate probit models by Geweke-Hajivassilou-Keane (GHK) simulated maximum likelihood methods. Our results show that climate change adaptations vary depending on which stresses individuals are responding to. At the household level, droughts and floods have the strongest effect on climate change adaptation. However, adaptations at the agricultural level depend more on the impacts of the stress and less so on the climatic strss itself. Understanding what climatic stresses are already eliciting a response, and what adaptations are being used by individuals, is invaluable for designing successful climate change policies. This understanding can also help policymakers identify where gaps exist in individual climate change adaptations and fill these gaps with a public response.